2015
DOI: 10.4103/0300-1652.169699
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic pattern of acquired heart diseases in Nigeria

Abstract: Background:Acquired heart diseases (AHDs) are present from childhood to old age, and the frequency of pathology differs according to age and the geographical region of the patients. The aim of this study was to document the echocardiographic patterns of AHDs in our setting.Materials and Methods:Retrospective analysis of echocardiographic diagnosis of AHD was done for age, sex, and echocardiographic pattern.Results:There were 190 diagnoses in the 163 patients with 27 patients having a double diagnosis, consisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…Only one patient had a diagnosis of Cor-pulmonale constituting 0.3%. This is similar to what was reported by Eyo et al in their study on Echocardiographic pattern of acquired heart diseases in Nigeria [17]. Several precipitating factors have been identified that may contribute to HF hospitalizations, viz: arrhythmia, myocardial ischemia, pneumonia, hypertension, worsening renal failure, and lifestyle modification or medication non-compliance [18] [19].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Only one patient had a diagnosis of Cor-pulmonale constituting 0.3%. This is similar to what was reported by Eyo et al in their study on Echocardiographic pattern of acquired heart diseases in Nigeria [17]. Several precipitating factors have been identified that may contribute to HF hospitalizations, viz: arrhythmia, myocardial ischemia, pneumonia, hypertension, worsening renal failure, and lifestyle modification or medication non-compliance [18] [19].…”
Section: Discussionsupporting
confidence: 89%
“…In addition patients with heart failure are susceptible to respiratory tract infection because of diminished ability of congested lungs to expel respiratory secretions [20]. Prescription non-adherence was previously reported as one of the important precipitants of heart failure as observed in this study [17] [18]. Other precipitants in this study were arrhythmia and anaemia with uncontrolled hypertension.…”
Section: Discussionsupporting
confidence: 54%
“…Echocardiography is a veritable tool for the diagnosis and characterization of Acquired heart diseases(AHD) 5,6 . The echocardiographic machine is currently available in all tertiary and some secondary health institutions in Sudan 7 . With the echocardiographic confirmation of AHD, a prognostication and management plan can confidently be made 8 .…”
Section: Introductionmentioning
confidence: 99%
“…With the echocardiographic confirmation of AHD, a prognostication and management plan can confidently be made 8 . Apart from diagnosing AHD for possible treatment, identification of heart diseases by echocardiography generally 9 . It also helps in the prognostication of patients needing noncardiac operations since perioperative morbidity and mortality are higher in those with structural heart disease than those without 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Nigeria's 0.5 operations per million (Ops/mio) are opposed by 177 Ops/mio in the Maghreb countries, both listed in similar GDP ranks. Nigeria is the most extreme lower-middle-income country with cardiac surgery barely existent for its population of 200 million in spite of a heavy burden of RHD (44,45). In this case, government commitment is the main reason for the difference.…”
Section: Introductionmentioning
confidence: 99%